The Influence of Infrastructure Management on Sports Development at State Polytechnics in Bandung - Dede Sujana (Soshum: Jurnal Sosial dan Humaniora, 2018)
Polytechnic as a higher educational institution trains students to be capable of becoming independent human. It is also responsible for equipping students with competence to compete in the workplace. Sport serves as a means of character and life skills development in students. It is well supported by the infrastructure management in Polytechnic. Based on the formulation of the problem mentioned above, the general purpose of this study is to determine the effect of infrastructure management on sports development in the State Polytechnic of Bandung. This study employed quantitative approach with survey method to obtain data from questionnaires and physical fitness test. The participants of the study are 77 students from two state polytechnics in Bandung. The result from data processing and analysis showed that 95.7% of sports participation rate is influenced by infrastructure management and the rest of 4.35 is influenced by other unexplainable variables, which means that facility and infrastructure management give positive influence on sports participation. In addition, other results showed that 93.0% of physical fitness figures are influenced by infrastructure management and 7.0% is influenced by other unexplainable variable, which means that infrastructure gives significant influence on physical fitness. It shows that if sports infrastructure is managed well, then it will greatly influence sports development.